Implementation of a national rapid prenatal exome sequencing service in England: evaluation of service outcomes and factors associated with regional variation - Ramakrishnan, Rema; Mallinson, Corinne; Hardy, Steven; Broughan, Jennifer; Blyth, Maisie; Melis, Gabriella; Franklin, Catherine; Hill, Melissa; Mellis, Rhiannon; Wu, Wing Han; Allen, Stephanie; Chitty, Lyn S.; et al. (Frontiers in Genetics, 2024)
IntroductionPrenatal exome sequencing (pES) can enhance genetic diagnosis of fetuses with structural anomalies and has recently been introduced as a national service in England. We aimed to examine service outcomes such as diagnostic yield (definite final diagnosis), referral rate, and sources of referral, and explore variation in outcomes of pES by individual or service level factors between 01 October 2021 and 30 June 2022.MethodspES testing results from the National Health Service laboratories performing testing were linked to National Congenital Anomaly and Rare Disease Registration Service data and the Maternity Services Data Set and descriptive statistics computed.ResultsThere were 475,089 women who gave birth in England during the study period. The referral rate for pES was 8.6 (95% CI 7.8, 9.4) per 10,000 maternities. About 59% of those referred proceeded with pES testing and 35% of women who proceeded received a definite final diagnosis with a median turnaround time of 15 days. Of those who had pES testing, 64.6% had a live birth, 25.3% underwent termination of pregnancy (median gestational age at termination: 26 weeks), and 9.3% had a stillbirth. Among the 85 women who had a definite final diagnosis, 40% had a termination of pregnancy, 18% had a stillbirth, and 42% had a live birth. The corresponding figures among women without a definite final diagnosis were 18%, 5%, and 78%, respectively. Among women who had a termination of pregnancy, the median gestational age at final report was 24.9 weeks and 26.2 weeks at termination. Variation observed in some of the characteristics and outcomes between regional services were limited by small sample size.ConclusionThis study showed that of those referred, pES testing provided a diagnosis for one in three pregnancies with a fetal anomaly across England during the study period when other tests had been non-informative. Women who opted for a termination of pregnancy underwent the procedure at relatively late gestations. Earlier referral for pES, streamlining pathways, and faster turnaround times may help results to be available at an earlier gestation to allow families more time to make decisions around continuing or terminating their pregnancy. The variation in service outcomes between regional services needs to be investigated further to understand the reasons for these differences.